Outcome and natural course of renal dysfunction in liver transplant recipients with severely impaired kidney function prior to transplantation. Issue 1 (1st February 2018) - Horvatits, T; Pischke, S; Proske, VM; Fischer, L; Scheidat, S; Thaiss, F; Fuhrmann, V; Lohse, AW; Nashan, B; Sterneck, M
Abstract : Background: Since introduction of the MELD score in the liver allograft allocation system, renal insufficiency has emerged as an increasing problem. Here we evaluated the course of kidney function in patients with advanced renal insufficiency prior to liver transplantation (LT). Methods: A total of 254 patients undergoing LT at the University Medical Centre Hamburg‐Eppendorf (2011–2015) were screened for renal impairment (GFR < 30 ml/min) prior to LT in this observational study. Results: Eighty (32%) patients (median 60 years; M/F: 48/32) had significant renal impairment prior to LT. Median follow‐up post‐LT was 619 days. Patient survival at 90 days, one year and two years was 76%, 66% and 64%, respectively. Need for dialysis postoperatively but not preoperatively was associated with increased mortality ( p  < 0.05). Renal function improved in 75% of survivors, but 78% of patients had chronic kidney disease ≥ stage 3 at end of follow‐up. Of eight (16%) survivors remaining on long‐term dialysis, so far only four patients have received a kidney transplant. Conclusion: Postoperative dialysis affected long‐term mortality. In 75% of survivors renal function improved, but still the majority of patients had an impaired renal function (CKD stage 3–5) at end of follow‐up. Future studies should elucidate the impact of kidney dysfunction and dialysis on recipients' long‐term survival.